Multiplatform analysis of the radiative effects and heating rates for an intense dust storm on 21 June 2007. Issue 16 (30th August 2013) - Naeger, Aaron R.; Christopher, Sundar A.; Johnson, Ben T.
Abstract : [1] Dust radiative effects and atmospheric heating rates are investigated for a Saharan dust storm on 21 June 2007 using a combination of multiple satellite data sets and ground and aircraft observations as input into a delta‐four stream radiative transfer model (RTM). This combines the strengths of the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations and CloudSat satellites and in situ aircraft data to characterize the vertical structure of the dust layers (5 km in height with optical depths between 1.5 and 2.0) and underlying low‐level water clouds. These observations were used, along with Aerosol Robotic Network retrievals of aerosol optical properties, as input to the RTM to assess the surface, atmosphere, and top of atmosphere (TOA) shortwave aerosol radiative effects (SWAREs). Our results show that the dust TOA SWARE per unit aerosol optical depth was −56 W m −2 in cloud‐free conditions over ocean and +74 W m −2 where the dust overlay low‐level clouds, and show heating rates greater than 10 K/d. Additional case studies also confirm the results of the 21 June case. This study shows the importance of identifying clouds beneath dust as they can have a significant impact on the radiative effects of dust, and hence assessments of the role of dust aerosol on the energy budget and climate. Key Points: The SWARE of dust is significantly influenced by low‐level clouds. Surface Albedo has a considerable impact on the SWARE of dust. Dust storms can cause significant warming in the atmosphere.